Effect of Pupal Exposure of Raisin Moth ,Ephestia figulilella (Gregson),(Lepidoptera:pyralidae) to High Temperature on Certain Biological Parameters of the Adult (Baghdad Science Journal, 2025)
The pupal stage of Ephestia figulilella was exposed to temperature of 40 ,45 and 50 ºC for different period (1,3 and 6 hrs) besides the control which exposed to 28 ºC .The effects of these temperature degrees were determined on some biological aspects of produced adult . Results showed that there is increasing in the percentage of dry dead pupa and malformed adults as the temperature and duration of exposure to it increased . Furthermore ,the mean number of eggs / female and the age percent of egg hatch for the following mating : ( exposed female × normal male , normal female × exposed male and exposed female × exposed male ) were also effected when adults exposed to these temperature as pupae .